A study of the relationship between "fatigability of acoustic reflex" and temporary threshold shift - Kamakshi (Journal of All India Institute of Speech and Hearing, 1970)
It has been generally recognized that there are individual differences in the susc~ptibilityof ears to damage from noise. Many references have been made in the literature to 'tough ears' and 'tender ears' referring to differences in degree of susceptibility.